Estudo e aplicações das funções hiperbólicas - Santos, Jonas José Cruz dos (2015)
This work intends to show the hyperbolic functions, analyzing their similarities and contrasts with the circular trigonometric functions. To this, we start showing a short review about the circular trigonometry and hyperbole, describing their main elements and properties. Then, we made a study about hyperbolic functions, with the de nitions of sine, cosine and the other hyperbolic functions and their main properties. We nished this work with some applications of these functions on everyday.